2013
DOI: 10.1080/10256016.2013.770393
|View full text |Cite
|
Sign up to set email alerts
|

Calcium isotope fractionation in liquid chromatography with crown ether resin in methanol medium

Abstract: Breakthrough mode liquid chromatography was employed to investigate calcium (Ca) isotope fractionation in methanol medium. Highly porous silica beads, the inner pores of which were embedded with a benzo-18-crown-6 ether resin, were used as column packing material. Enrichment of heavier isotopes of Ca was observed in the frontal part of the respective Ca chromatograms. The values of the isotope fractionation coefficient (ϵ) were in the order of 10(-3) at 25 °C. Use of methanol as solvent has little advantage ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…The findings in Table 2 and Figures 2-5 may be summarized as follows: were obtained with the B18C6 resin; they are on the same order as those of the previous studies with the same resin [17][18][19][20], and larger than those of the studies with ion exchange resins [3,4] and with the B15C5 resin (benzo-15-crown-5 ether resin synthesized in the inner pores of highly porous silica beads [11]) [19]. (3) The ε value seems, admittedly roughly, nearly proportional to the isotopic mass difference, M. In other words, the ε/ M value is nearly constant in a given run.…”
Section: Ca Isotopic Datasupporting
confidence: 67%
See 2 more Smart Citations
“…The findings in Table 2 and Figures 2-5 may be summarized as follows: were obtained with the B18C6 resin; they are on the same order as those of the previous studies with the same resin [17][18][19][20], and larger than those of the studies with ion exchange resins [3,4] and with the B15C5 resin (benzo-15-crown-5 ether resin synthesized in the inner pores of highly porous silica beads [11]) [19]. (3) The ε value seems, admittedly roughly, nearly proportional to the isotopic mass difference, M. In other words, the ε/ M value is nearly constant in a given run.…”
Section: Ca Isotopic Datasupporting
confidence: 67%
“…The smallness of the deviation of the experimental slope from the theoretical one supports that the isotope effects in the present systems are normal mass-dependent ones. We note, however, that in some experiments of our present and previous papers [19,20], the ε/ M value is found to be larger for the 43 Ca/ 40 Ca isotopic pair than for the other pairs beyond experimental uncertainties. .…”
Section: Ca Isotopic Datacontrasting
confidence: 67%
See 1 more Smart Citation
“…Lauth and Gramain reported that the performance of the cation separation strongly depends on the chemical structure of the bound crown ether, and on the preparation process and the choice of the silica support . Recently, a porous silica bead embedded with benzo-18-crown-6 ether was used for the selective separation of Ca 2+ ions. , …”
Section: Introductionmentioning
confidence: 99%
“…Crown ethers are a class of compound that can form very stable molecular ensembles or complexes with alkaline and alkaline earth metals (Pedersen 1967;Stover 1984;Høiland et al 1979). The previous literature has reported that benzo-18crown-6 ether has been successfully used for the selective separation of Ca 2þ relative to other alkali metal cations (Capel-Cuevas et al 2009;Okumura et al 2015;Nemoto et al 2013). The PES membrane is an excellent performance material for membrane separation due to its superior mechanical and chemical properties (Liu et al 2011).…”
Section: Introductionmentioning
confidence: 99%